Component-wise testing of laser written integrated coupled mode beam splitters - Guan, J; Menssen, A; Liu, X; Wang, J; Booth, M (Optical Society of America, 2019)
Photonic integrated circuits (PICs) are important enabling technologies for the developments of areas such as quantum information processing (QIP). Coupled-mode integrated beam splitters (IBS) are widely used in many PICs, so direct and accurate testing of individual IBSs inside a PIC is increasingly desirable, as the development of PICs for QIP is scaled up. Here we demonstrate a solution for component-wise testing of coupled-mode IBSs without limitations on component location and PIC architectures. The method is based on the imaging of an individual IBS with a custom-built multifunctional adaptive optical microscope, combined with the calculation of its beam-splitting ratio through numerical modelling.